Relation between nitrogen source and plant growth regulators on tomato growth and nutrient uptake - Magalhães, José R.; Wilcox, Gerald E. (Pesquisa Agropecuaria Brasileira, 2014)
Tomato plants (Lycopersicon esculentum L.) were grown in sand culture with NH4+ or NO3- sources of N and four plant growth regulators (Cytokinine (CK), Trycotanol (TCOT), ABA (Abscisic acid) and Cycocel (CCC)). In general, the plant growth regulators had no significant effect on tomato growth except CCC which reduced dry weight in plants supplied with NO3-. Ammonium reduced plant growth as compared to NO3-, for all treatments but CCC. The cations K, Ca and Mg content in tissue decreased with NH4+ treatment as compared to NO3-. However Trycotanol tended to reduce this effect by increasing Ca in plants. CCC enhanced nitrate content in plant shoot supplied with NO3-, but had no effect on plants supplied with NH4+. Every plant growth regulator increased free NH4+ in plant shoots supplied with that N source.